Nature Reviews Molecular Cell Biology - Baumann, Kim.; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Research.)
Nature Reviews Molecular Cell Biology is the leading monthly review journal in the field of molecular and cell biology. With its extraordinary breadth and depth of coverage, the journal provides a unique resource of information, opinion and commentary for cutting-edge molecular and cell biology research. All Reviews, Perspectives and Progress articles are carefully commissioned, written by leaders in the field, and subject to rigorous peer review $1 (Bwhich results in timely and authoritative articles. In addition, articles are edited and the diagrams redrawn by professional art editors, which makes for highly readable, visually attractive articles that are accessible to specialists and non-specialists alike.s
Keywords: Cancer research; Life sciences; Biochemistry; Cell biology; Stem cells; Developmental biology; Life Sciences, general; Cell Biology; Cancer Research; Developmental Biology; Stem Cells; Biochemistry, general